Does Preoperative Weight Change Predict Postoperative Weight Loss after Laparoscopic Roux-en-Y Gastric Bypass in the Short Term? - Dan Eisenberg; Andrew J. Duffy; Robert L. Bell (Hindawi Limited, 2010)
Background. Many institutions mandate preoperative weight loss prior to bariatric surgery. This study examines the correlation between preoperative weight change and postoperative success following laparoscopic Roux-en-Y gastric bypass. Methods. We retrospectively studied the correlation between change in BMI before surgery and change in BMI postoperatively, using linear regression analyses and one-way ANOVA, in 256 consecutive gastric bypass patients with 1-year followup. Results. Of 256 patients, 125 lost weight preoperatively (mean −1.7% BMI), while 131 maintained or gained weight (mean +1.2% BMI). Postoperatively, there was no significant difference in percent BMI loss between the two groups (34.6% and 34.5%). The percent change in BMI preoperatively did not predict postoperative BMI change after 1 year (𝑃=n.s.). Conclusions. Our study did not show any correlation between preoperative weight change and postoperative weight loss after Roux-en-Y gastric bypass. Therefore, we do not believe that potential patients should be denied bariatric surgery on the basis of their inability to lose weight preoperatively.